Establishing the legal framework for resolving private International Law issues arising from matrimonial disputes in Malaysia - Hamid, Abdul Ghafur@Khin Maung Sein; Mohd Zin, Najibah; Abdul Hak, Nora; Mohamed Jani, Hidayati (2019)
The research is primarily concerned with conflict of jurisdiction and conflict of laws in matters relating to matrimonial disputes in Malaysia. In conversion cases, the burning issue is whether the civil or Shari’ah Court has exclusive jurisdiction to grant degree of divorce and to make other ancillary orders. Parental child abduction is another worrisome issue. In view of the increasing number of high profile cases where much public interest are at stake, the primary objective of this research is to conduct an in-depth and comprehensive investigation on the matter to be able to come out with viable solutions, which is acceptable to all stake holders to achieve the purpose of national unity. The research is mainly based on qualitative approach. Apart from analysis of legislation and case law, primary data has been collected through in-depth interviews and round-table discussions, involving AG’s Chambers, Civil and Shari’ah Judiciary, JAKIM, IKIM, Islamic Religious Departments and other stake holders.